Workers' Compensation: Wage Effects, Benefit Inadequacies, and the Value of Health Losses - Viscusi, W. Kip; Moore, Michael J. (The Review of Economics and Statistics, 1987)
W. Kip Viscusi, Michael J. Moore, Workers' Compensation: Wage Effects, Benefit Inadequacies, and the Value of Health Losses, The Review of Economics and Statistics, Vol. 69, No. 2 (May, 1987), pp. 249-261